Domestic Reindeer Herding in Arctic Regions of Yakutia in Second Half of 1990s: Experience of Decision-Making on Socio-Economic Issues in Industry - Ya. M. Sannikova (Научный диалог)
The experience ofsolving social and economic problems related to domestic reindeer herding in the Arctic regions of Yakutia during the early post-Soviet period is being studied. Attention is given to the adoption of the first program document in the republic— Resolution No. 521, dedicated to comprehensive support for traditional industries and social protection of workers in the Arctic regions. Archive documents on the activities of the relevant ministry in developing recommendations on wage payment in reindeer herding, adopting new decisions on one-time payments to reindeer herders and tent workers, and statistical data on some general economic indicators in reindeer herding are presented. The approach to calculating labor standards for reindeer herders and attempts at their social protection through professional tariffication of wage payment are presented in detail. Social directions included officially in the program for the development of domestic reindeer herding are highlighted. At the local level, it is shown that representatives of the relevant ministry responsible for managing traditional industries could not always rely on a positive experience in making decisions on socio-economic development of domestic reindeer herding as a leading traditional occupation of indigenous people, but they were fully aware of the real social situation of workers in the industry.